Cottin M. y Faría, R. (2008). El Libro Negro De Los Colores. Barcelona-Buenos Aires - Ciudad De México: Libros Del Zorro Rojo. 28 páginas. ISBN: 978-84-92412-19-8 - Arellano , Paula Virginia; Hug, Mercedes Ximena; Pinardi, Lilian Carolina (Traslaciones. Revista latinoamericana de Lectura y Escritura, 2021)
.